Crop genetic erosion: understanding and responding to loss of crop diversity - Khoury, Colin K.; Brush, Stephen; Costich, Denise E.; Curry, Helen Anne; Haan, Stef; Engels, Johannes M. M.; Guarino, Luigi; Hoban, Sean; Mercer, Kristin L.; Miller, Allison J.; Nabhan, Gary P.; Perales, Hugo R.; et al. (The New phytologist, 2022)
Summary Crop diversity underpins the productivity, resilience and adaptive capacity of agriculture. Loss of this diversity, termed crop genetic erosion, is therefore concerning. While alarms regarding evident declines in crop diversity have been raised for over a century, the magnitude, trajectory, drivers and significance of these losses remain insufficiently understood. We outline the various definitions, measurements, scales and sources of information on crop genetic erosion. We then provide a synthesis of evidence regarding changes in the diversity of traditional crop landraces on farms, modern crop cultivars in agriculture, crop wild relatives in their natural habitats and crop genetic resources held in conservation repositories. This evidence indicates that marked losses, but also maintenance and increases in diversity, have occurred in all these contexts, the extent depending on species, taxonomic and geographic scale, and region, as well as analytical approach. We discuss steps needed to further advance knowledge around the agricultural and societal significance, as well as conservation implications, of crop genetic erosion. Finally, we propose actions to mitigate, stem and reverse further losses of crop diversity.